A beetle is shy - Aston, Dianna Hutts (Chronicle Books, 2016)
"The award-winning duo of Dianna Hutts Aston and Sylvia Long team up again, this time creating a gorgeous look at the fascinating world of beetles. From flea beetles to bombardier beetles, an incredible variety of these beloved bugs are showcased here in all their splendor." --